RELATIONSHIP AND INTERACTION OF INTERNATIONAL PUBLIC, INTERNATIONAL PRIVATE LAW AND NATIONAL LAW - Baikovs, Aleksandrs; Bulgakova, Ilona (Administrative and Criminal Justice, 2019)
The purpose of this paper is to analyze the interplay between international public and private law and national law, and to provide an assessment of the theory of public and private law and its interrelationship.Private international law is closely linked to public international law. However, if public international law is an autonomous system of law, then private international law is an integral part of national law, since it governs cross-border private law relations.The objectives of the study stem from its purpose, namely:to clarify the nature and understanding of international public and private law; to clarify the relationship between international public and private law and national (internal) law. The object of the research is the problems of the relation and interrelation of international public and private law.As a result of the study, several conclusions were drawn, which are as follows: 1) public international law is an independent legal system, but private international law is an integral part of national law; 2) there is a relationship between public international law and private international law; 3) general theoretical categories and concepts are partly incompatible with the nature of both international public and private international law; 4) the value, validity, and credibility of contemporary theoretical research in international law largely depends on the inclusion of relevant categories andThe following methods have been used in the research: analysis and synthesis, induction and deduction, abstracting, generalization, analogy, idealization, formalization, axiomatic method, systematic and historical research.